Cicero about Translation: Exploring the Meaning of Words - Kučinskienė, Audronė (Literatūra, 2012)
[full article in Lithuanian; abstract in English]The author of the article reveals Cicero’s attitude towards translation, exploring some passages from his rhetorical and philosophical treatises which deal with translation from Greek to Latin, and paying most attention to the usage of words with the meaning “translate, translator”.To conclude, the regular Latin verb for “to translate” (con)vertere in Cicero’s usage implies neither the accuracy or literalism of translation. For a close literal translation he uses interpretari or such expressions as ad verbum (verbum de verbo verbum e verbo, ad verbum) exprimere, verbum pro verbo reddere. The verbs exprimere, explicare, reddere are used more or less metaphorically to express various aspects of translation from Greek, which includes also a free interpretation of the original and borrowing some elements from the original. According to our observations, Fin. I. 7 is the only case in Cicero’s extant scripts, as well as the first in Latin literature, when the verb transferre, while meaning “to transfer, to borrow, to use in context” comes closest to vertere. By contrast, the authors of I–II AD, such as Seneca, Pliny the Elder and the Younger, Quintilian use the word transferre with the meaning of translation quite regularly.We argue that when Cicero calls himself not interpres, sed orator, he tries to indicate first of all not the closeness or freedom of translation, but rather the rhetorical power of his text. He is not afraid to use a word in not a very common sense, or two words for one in the original, or to create a new one if necessary, which may seem too bold for the interpretes indiserti not so skilled and well-trained in rhetorics. Cicero approached his work of translation without any preconceived rules, and the main standard referred to is his own taste based on the ruling principle of rhetorics – decorum, aptum, prepon – i.e. appropriateness. Cicero, as a translator as well as an orator, matches every word, rhetorical figure and phrase to the style, conception and situation of the work in order to express most effectively vim orationis. In other words, converti ut orator means converti optime.Yet more, to translate as orator means to convey to the reader the original function of the source text and to make it act in the new cultural context of the translation language. In the case of De optimo genere oratorum, the Latin translation of the Demosthenes’ and Aeschines’ orations must become a weapon in Cicero’s polemics with the Neoatticists and persuade the Roman audience to value critically their limited eloquence. A really good translation, on the one hand, enables the author of the source text to speak throught it (Aeschinem ipsum Latine dicentem audiamus; Opt. gen. 23), on the other, such a translation manages to displace the original work: to learn the Attic rhetoric, Roman youths will be able to turn to the Latin translation made by Cicero, which must become a standard for the other Roman orators (erit regula, ad quam eorum dirigantur orationes qui Attice volent dicere; Opt. gen. 23).
Keywords: none